Muhammadiyah's Da’wa in Print Media in the Early 20th Century: A Case of Bintang Islam Magazine, 1924-1927 - Adam, Yusril Fahmi; Tamam, Mundzir (Buletin Al-Turas, 2025)
PurposeThis research aims to provide an in-depth analysis of the Islamic outreach efforts of Muhammadiyah, one of Indonesia's largest Islamic organizations, as documented in the magazine Bintang Islam during the years 1924-1927.    MethodThe study employs a historical method comprising four stages: heuristic, verification, interpretation, and historiography.  Primary sources primarily include issues of Bintang Islam from 1924-1927, supported by relevant secondary sources such as books and journals.  These sources were critically examined for authenticity, interpreted, and then synthesized into a historical reconstruction during the historiographical phase. The analysis integrates approaches from sociology of mass communication and hermeneutics, emphasizing an analytical-descriptive framework.   FindingsThe findings reveal that Bintang Islam, founded by Muhammadiyah, served as a representation of Islamic press.  Its establishment signified the continuity of modernism influenced by the Dutch East Indies and the impact of Islamic ideologies introduced by pilgrims, scholars, and the reformist ideas of Jamaluddin Al-Afghani, Muhammad Abduh, and Rashid Rida. Within Bintang Islam, Muhammadiyah figures articulated their da’wa thoughts, including efforts to counter Christianization, advocacy for renewal (tajdid), enjoining good and forbidding evil (amar ma'ruf nahi munkar), and excerpts on international da’wa activities.   Conclusion  In conclusion, Muhammadiyah's da’wah through Bintang Islam represents its response to widespread evangelization efforts, particularly in Java, addressing the decline in Muslim practices due to superstitions, innovations, and un-Islamic practices. It also served as a catalyst for enhancing religious, social, economic, and political awareness.